Significance of Mirror Neurons in Surgical Skills Training: A Novel Perspective - Jamkar, Maya; Telang, Shweta; Jamkar, Arun (Research Highlights in Disease and Health Research Vol. 7, 2023)
This paper propounds the potential utilization of cognitive functioning of Mirror neurons to the psychomotor domain of surgical skill enhancement. This will not only open new concepts in skill learning for apprentice surgeons but will also the surgical proficiency of skilled surgeons. Italian researchers discovered in the early 1990s that the monkey brain contains a special class of cells that fire when it sees or hears an action and when it performs the same action on its own. These cells were dubbed "Mirror Neurons." Following human research, it was discovered that the human brain has multiple mirror neuron systems that specialise in carrying out and comprehending actions, intentions, emotions, and behaviour. The available scientific literature provides substantial evidence that Mirror neurons offer the basis to grasp the actions and intentions of others through direct imitation without the need for any conceptual reasoning. The discovery of Mirror neurons has added a new light to the understanding of culture, empathy, philosophy, language, imitation and autism. The present paper gives a brief overview of the myriad applications of the concept and mechanism of mirror neurons. Here, we present an innovative concept of harnessing the functional mechanism of Mirror neurons to the domain of psychomotor surgical skill development essential for surgeons. We have illustrated this concept by extracting references and thought-models from previous works. However, none of the previous works have demonstrated the utility of application of Mirror mechanism in surgical training.